2021
DOI: 10.1017/s0967199421000277
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induced by methomyl exposure reduces the quality of early embryo development in mice

Abstract: Summary Methomyl is a widely used carbamate insecticide and environmental oestrogen that has adverse effects on the reproductive system. However, there have been no reports on the effect of methomyl on early embryos in mammals. In this study, we explored the effect of methomyl exposure on the quality of early embryonic development in mice and the possible mechanisms. During in vitro culture, different concentrations of methomyl (10, 20, 30 and 35 μM) were added to mouse zygote medium. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Imidacloprid impairs movement in the Procambarus clarkii digestive system through oxidative stress and neurotoxicity ( Huang et al, 2021 ). Methomyl exposure increases oxidative stress and damages mitochondrial function in mice ( He et al, 2021b ). Beta-cypermethrin influences reproduction by increasing oxidative stress in the uterine tissue of female mice ( Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imidacloprid impairs movement in the Procambarus clarkii digestive system through oxidative stress and neurotoxicity ( Huang et al, 2021 ). Methomyl exposure increases oxidative stress and damages mitochondrial function in mice ( He et al, 2021b ). Beta-cypermethrin influences reproduction by increasing oxidative stress in the uterine tissue of female mice ( Zhou et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, the larvae of Pacific abalone Haliotis discus hannai were exposed to moderate hypoxia (3–4 mg/L) from zygotes to trochophores, and the growth rate and hypoxia tolerance were evaluated. The zygote and embryo stages are selected as the starting points of hypoxia exposure because the organisms undergo a host of complex morphological changes and physiological processes during these stages, including cell division, cell differentiation, and organogenesis, and are relatively sensitive to environmental stimulations such as hypoxia, temperature variations, and pollutants. The trochophore stage was selected as the end point of hypoxia exposure because the behavior patterns and dissolved oxygen demand of larval abalone as well as the oxygen regimes that they encounter before and after hatching vary a lot. , Before hatching, the trochophore cannot move freely and relies on yolk nutrition with a relatively high critical PO 2 . However, the trochophore after hatching can swim freely and agitate water by cilia awing with a relatively low critical PO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the in vivo growth environment has been extensively simulated during the IVC process, the developmental potential and quality of pig embryos produced in vitro remain lower than those produced in their bodies (Bauer et al, 2010). Previous studies have confirmed that the long-term accumulation of reactive oxygen species (ROS) in embryos during IVC is an important factor affecting the quality of in vitro-generated embryos (He et al, 2022;Luo et al, 2021). ROS can lead to many problems, including DNA damage, mitochondrial dysfunction, ATP depletion, cell apoptosis, and embryonic development arrest.…”
mentioning
confidence: 99%